Relations Between the Knowledge of Education and Training (Pedagogy), and the Knowledge of Humankind (Anthropology) in Comenius, Rousseau and Kant: Contributions of Pedagogical Anthropology - Andrés Klaus Runge Peña; Diego Alejandro Muñoz Gaviria; Carlos Ospina Cruz (Universidad Pedagógica Nacional, 2016)
The article proposes that there is no education without anthropological considerations, and there is not anthropology without pedagogical considerations. Through the reading of three classic authors  -Comenius, Rousseau and Kant- the authors analyze the links between anthropological knowledge and pedagogical knowledge that would have arisen in modern times, a period in which the education became a matter of systematic reflection which led to the pedagogical thinking into anthropological reflections.